Prevalence and Intensity of Salmincola edwardsii in Brook Trout in Northwest New Brunswick, Canada. Issue 1 (21st January 2020) - White, Carson F. H.; Gray, Michelle A.; Kidd, Karen A.; Duffy, Michael S.; Lento, Jennifer; Monk, Wendy A.
Abstract: Parasites can compromise the health and fitness of individual fish, and it is important to generate baseline information that can then be used to document changes in the abundance and distribution of potentially pathogenic parasites. The ectoparasitic copepod Salmincola edwardsii was assessed with respect to prevalence (percentage of infected fish per site), infection intensity (number of parasites per infected fish), and attachment location on Brook Trout Salvelinus fontinalis in northwest New Brunswick, Canada. Ten sample sites were assessed, with six sites on two streams in the Quisibis River basin and four sites on three streams in the Restigouche River basin. Parasite species identity was supported by 100% sequence identity with S. edwardsii in a variable region within 28S rDNA. The prevalence of fish infected per site ranged from 19.0% to 79.6%, with an overall prevalence of 48.5 ± 19.1% (mean ± SD) per site. Mean infection intensity was 1.5 ± 0.9 copepods/fish (range = 1–7), with parasites almost exclusively surrounding the dorsal fin and/or adipose fin (97.6%). There was no influence of trout age‐class on parasite prevalence. Some fish presented with fin erosion at the site of parasite attachment (12.5%), and 6.2% also presented with hyperplastic skin lesions where no parasites were observed, that could be misinterpreted as secondary bacterial or fungal infections. Skin and fin damage were significantly more common when fish were infected with three or more individual parasites. The pathogenic potential of this parasite makes its presence noteworthy as a risk to salmonids that are both recreationally and ecologically important.